An improved sensitivity-based coordination method using optimum sensitivity and its application to structural optimization of an unmanned aerial vehicle family. Issue 3 (4th March 2021) - Zou, Jun; Yao, Weixing; Xie, Jiang; Mou, Haolei
ABSTRACT: This article discusses important improvements in the sensitivity-based coordination method (SCM) for the optimization of product family or quasi-separable problems. In this method, first presented by Zou et al. [ Engineering Optimization 48(7), 2016], the system level coordinates each subsystem based on sensitivity information. Test results suggest that the SCM is robust and efficient; however, for complex engineering problems the computing cost is significant. In this article, the SCM is improved by adopting the optimum sensitivity derivatives as the sensitivity information for global objective F in the system level. The performance of the improved SCM is demonstrated by a numerical test example, and the results show that the solutions and computational efficiency are both improved. The potential of the improved SCM is then demonstrated by structural optimization of the wings of an unmanned aerial vehicle family. The difference between the individual design and family design of wing structures is further investigated.